Prevalence of the major diseases in Penaeus vannamei farmen of Sinaloa Mexico - Morales Covarrubias, María Soledad; García-Aguilar, Noemí; Bolán-Mejía, María del Carmen; Zamora-García, Oscar Guillermo (SaberULA, 2020)
The aim of this study was to determine the prevalence and severity of the diseases: acute hepatopancreatic necrosis disease (AHPND), necrotizing hepatopancreatitis (NHPB) caused by intracellular bacterium (Hepatobacter penaei), septic hepatopancreatic necrosis (NHPS), and the white spot syndrome virus (WSSV) in farmed shrimp during two productive cycles (spring and summer) in the years (yrs) 2016 and 2017. From 360 studied shrimps, 90% showed external characteristics of apparently healthy animals, while only 10% of the specimens presented red coloration, soft cuticle, and muscular opacity. AHPND was the disease with the higher average prevalence for all the studied zones and seasons, with a prevalence of 53.33% in 2016 and 60.16% in 2017, followed by NHPS with 36.66% in 2016 and 42.83% in 2017. The incidence of WSSV was the lowest compared to the other diseases studied in this work, with 16.16% in 2016 and 20% in 2017; NHPB was only observed in summer with an average prevalence of 16.16% for both yrs. The northern area of Mexico registered the highest rates of mortality associated to these diseases, excluding WSSV, which resulted in being the most prevalent disease in the southern area (although such difference it is not statistically significant). The specimens diagnosed with AHPND exhibit severe damage in hepatopancreas as well as cellular detachment in the intestinal proximity. The organisms with NHPS showed multifocal cellular detachment in hepatopancreas and bacteria growth in heart, gills, lymphoid organ, connective tissue and muscles. The physicochemical variables considered for this study did not show significant variability among the zones and seasons analyzed, however, any alteration on these parameters might cause stress in the shrimps impairing the immune response against opportunistic pathogens. The presence of bacterial and viral diseases identified in this work is likely related to a low quality of the post-larvae, or an inadequate farming environment.
Prevalencia De Las Principales Enfermedades En Penaeus Vannamei De Cultivo En Sinaloa, Mexico
Keywords: Enfermedades; AHPND; WSSV; NHPS; NHPB; Camarones; Universidad del Zulia (LUZ); Universidad de Los Andes (ULA); Diseases; AHPND; WSSV; NHPS; NHPB; Shrimp; Revista Científica; Revista Científica: Fauna Silvestre; Medio Ambiente; Revistas